Teacher creativity and innovation influence the quality of learning, which impacts learning achievement in physical education - Pahlawani, Kania Agustina; Nining, N (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Physical education in schools contributes to students' physical and mental health. To produce learning achievement in this subject, teachers must design unique and effective methods. This research aims to determine the role of teacher creativity and innovation in influencing the quality of learning which has an impact on learning achievement at MTs in Cikijing District, Majalengka Regency. The research design was quantitative, using an explanatory survey of 92 teachers in four sub-districts using a questionnaire instrument. Data analysis was carried out descriptively and verifiably through path analysis. Research findings show that teacher creativity, which encourages new learning methods, synergizes with teacher innovation, opens the door to more effective teaching approaches, and the improved quality of learning positively impacts student achievement. The implications of this research include developing training programs and adapting educational policies to support teachers in implementing innovation and creativity, providing practical guidance for educators and policies to improve the quality of learning and student achievement.